Production of the surface layer of workpieces during electrochemical and combined machining - A.I. Boldyrev (Advanced Engineering Research)
The article deals with the generation of surface layer by dimensional electrochemical and combined machining. It shows that it is possible to achieve the required performance criteria of surfaces with predetermined properties with the help of the optimum combination of processing characteristics of different processes during combined machining.